'Graphic Resurgence': The return of the early Gothic comic strip in trans-medial discourse. Issue 1 (1st April 2014) - Jones, David Annwn
Though those types of publications that are popularly called the Gothic comic book and Gothic graphic novel comprise one of the graphic medium's most successful genres and, though celebrated examples of the work such as Neil Gaiman's creations and David Finch's Batman The Dark Knight series (2012–) have begun to feature amongst topics for Gothic Studies conferences and anthologies, there seems as yet to be considerable critical amnesia about the genre's origins, the nineteenth-century sequential strip in general and their relations with contemporaneous Gothic publications. This study starts with a comparison of the depiction of a monstrous Gothic anti-hero in a narrative strip from the late 1840s with a similar celebrated figure from a 1990s Goth publication as a way of questioning assumptions about the exclusively formative role of American 1950s comic books in this context. This study then provides both a general overview of a vast and often overlooked field of graphic production pre-1900 and, in places, a frame-by-frame analysis of groundbreaking graphic techniques used by Gothic nineteenth-century artists. As well as discussing works as various as Joseph Franz von Götz's Lenardo and Blandine (1783), Gustave Doré's History of Holy Russia (1854), the Gothic graphic art of William Makepeace Thackeray and Rodolph Töpffer, Wilhelm Busch and G. Montbard's The Legend of John Belin (1874), my study seeks to reinstate the importance of these works of Gothic sequential visual art in relation to recent graphic novels and starts to define exciting possibilities for a synergetic interface between Comic Strip Studies and Gothic Studies.